2014
DOI: 10.1016/j.medici.2014.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Atherogenic index as a predictor of atherosclerosis in subjects with familial Mediterranean fever

Abstract: Elaboration of clinical models of inflammation-induced atherogenesis may further advance our knowledge of multiple inflammatory pathways implicated in atherogenesis and provide a useful tool for cardiovascular prevention. We believe that the atherogenic index also be used as a preliminary indication of accelerated atherosclerosis in FMF. However, large-scale prospective studies on this issue are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 18 publications
3
29
0
3
Order By: Relevance
“…The difference between two groups was not statistically significant in terms of GSTT1 and GSTM1 gene polymorphisms (p>0.05). GSTP1 Ile105Val polymorphism frequencies were 55% (n=33), 36 Table 4. The possible association between combined genotypes and CIMT, and triple genotype analysis was not investigated because of the possibility of low statistical power.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference between two groups was not statistically significant in terms of GSTT1 and GSTM1 gene polymorphisms (p>0.05). GSTP1 Ile105Val polymorphism frequencies were 55% (n=33), 36 Table 4. The possible association between combined genotypes and CIMT, and triple genotype analysis was not investigated because of the possibility of low statistical power.…”
Section: Resultsmentioning
confidence: 99%
“…In the studies which showed higher CIMT value in FMF patients, Ugurlu et al 41 have found statistically significantly lower HDL and LDL levels and Bilginer et al 34 found statistically insignificant LDL and significantly higher HDL in FMF patients compared to healthy controls. Acay et al 36 have detected higher LDL level in FMF patients but the difference between patients and controls was not statistically significant. In their study, HDL cholesterol was statistically significantly lower in FMF patients.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…Acay et al detected significantly higher TG/HDL-C ratio in patients with FMF versus healthy population [35]. However, the correlation between TG/HDL-C ratio and endothelial dysfunction in CID cases has not been fully clarified.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly fascinating is the impaired autophagic clearance of inflammasomes associated with common mutations in the MEFV gene found in patients with Familial Mediterranean Fever (58). This relatively common genetic disorder results in IL-1β hypersecretion (61) and increased atherogenesis (62, 63). We believe these studies collectively constitute sufficient evidence to distinguish autophagic clearance of inflammasomes from “bulk” autophagy and propose the term “inflammasomophagy” to refer to this selective process (Figure 3).…”
Section: Autophagic Degradation Of Inflammasomes By “Inflammasomophagy”mentioning
confidence: 99%